Updated β-correction Spectrophotometric Investigation of Zinc Chelate Solution with Acid Chrome Blue K and Determination of Zinc - Gao, Hang-Wen (Asian Journal of Chemistry, 2010)
The updated analysis of zinc chelate solution with acid chrome blue K(ACBK) of pH 8.5 has been studied using β-correction spectrophototmetry.In the determination of this chelate characteristic factors are involvedcontaining the complexation ratio, the real molar absorptivity (εγ) andeffective percentage of ligand. Besides, because of high sensitivity thechelate reaction is used for the determination of trace amounts of zinc. Theresults show that the chelate formed is expressed as Zn(ACBK)2 and itsεγ= 4.37 X 104 L·mol-1 cm-1 at 530 nm which is 3.6 times of its apparentvalue.